STRATEGY ANALYSIS TO FACE HOTEL COMPETITION IN THE NEW NORMAL COVID 19 ERA (Case study on Sinabung Hills Berastagi) - Dina Octavia; Dina Khairani (SEAN Institute, 2023)
The purpose of this study is to analyze strategies to face hotel competition in the new normal Covid-19 era at Sinabung Hills Berastagi Hotel and to determine the extent to which the strategy carried out by the management has an impact on the company. The research method used in this study is descriptive/qualitative techniques that describe the description of promotional data conducted by Sinabung Hills Berastagi Hotel during the new normal, using observation guidelines, interviews, and documentation. The results showed that Sinabung Hills Berastagi Hotel conducted a strategy to reduce operational expenditure and also provide discounted promos to attract customers. Promotional Media used are email, Whatsapp, and also online ordering applications. From the promotional media used, online booking applications show more of a good impact on the company.